Variable penetrance of a familial progressive necrotising encephalopathy due to a novel tRNAIle homoplasmic mutation in the mitochondrial genome. Issue 5 (30th April 2004) - Limongelli, A; Schaefer, J; Jackson, S; Invernizzi, F; Kirino, Y; Suzuki, T; Reichmann, H; Zeviani, M
Abstract : Introduction: We present a family comprising a clinically normal mother and two daughters, each with severe encephalopathy with onset in late childhood. A third daughter had died previously of an earlier onset but neuropathologically similar disease. Methods: Sequence analysis of the entire mtDNA was carried out in muscle, fibroblasts, and lymphocytes of the affected daughters and unaffected mother. Biochemical analysis of individual respiratory chain enzymes was performed on the same tissues, and on several transmitochondrial cybrid clones containing the nucleus of a 143B.206 osteosarcoma cell line and the mutant mtDNA. Results: Genetic analyses revealed in both daughters and mother the presence of a novel mutation in the tRNA Ile gene of mtDNA, which was homoplasmic in fibroblasts, lymphocytes, and skeletal muscle of the two patients. It was also homoplasmic in fibroblast and skeletal muscle samples of the mother, and approximately 97% heteroplasmic in her lymphocytes. Combined defects of complexes I and IV of the mitochondrial respiratory chain were found not only in fibroblasts of the two probands, but surprisingly also in those of their clinically unaffected mother. The respiratory chain defect segregated in transmitochondrial cybrids containing the nucleus of a 143B.206 osteosarcoma cell line and the mutant mtDNA, indicating that the latter was responsible for the biochemical phenotype. Discussion: Our results support the concept that homoplasmic mutations in tRNA genes can be responsible for mitochondrial disorders characterised by extremely variable penetrance. Albeit still unexplained, this phenomenon has important consequences in the nosological characterisation, clinical management, and genetic counselling of mitochondrial disorders.